Implementation of TK Ibnu Sina Batam's Company Profile Using Visitor-Based User Experience Method - Veza, Okta; Arifin, Nofri Yudi (YCMM, 2023)
The objective of this study is to implement the Company Profile of TK Ibnu Sina in Batam using a user experience (UX) approach that emphasizes visitor interaction and responsiveness. The utilization of this method aims to enhance positive interaction between visitors and the information presented within the company's profile. Through design considerations that take into account user needs and preferences, along with a focus on an intuitive and responsive interface, this research seeks to create an improved visitor experience in understanding the values, vision, and mission of TK Ibnu Sina. The outcomes of implementing the user experience method are expected to enhance visitor understanding of the company and bolster a positive corporate image within the public eye.